Energy balancing mechanisms for decentralized routing protocols in wireless sensor networks - Saleh, Ahmed Mohammed Shamsan (2012)
In Wireless Sensor Networks (WSNs), the sudden “death” of critical nodes can cause an entire network to malfunction. This is usually caused by uneven depletion of battery power of the individual nodes. In an unbalanced network, while critical nodes experience heavy traffic load which depletes their energy fast and die out, nodes in sparse regions in terms of data traffic continue to enjoy high energy levels. Therefore,this thesis investigates a method to balance and minimize usage of energy in sensor nodes, especially during routing. This is because network activities start to be challenged when the first sensor node exhausts its battery. Hence the proposed routing protocols in this thesis balances the rate of energy dissipation of the sensor nodes across the network and prevents sensor nodes from directly transmitting to far-off nodes, in most cases,when forwarding data to the sink, as this will cost unnecessarily high-energy expense. Thus, our main goal in this thesis is to develop a decentralized energy balancing and locally managed schemes to prolong the lifetime of WSNs and increase its reliability to network dynamics. This thesis presents three decentralized algorithms that are robust,scalable, and can be successfully executed in sensor networks. The first scheme is a SensorAnt, which is a self-optimization mechanism for WSN. It is able to utilize and optimize the sensor nodes’ resources, especially the batteries, to achieve balanced energy consumption across all sensor nodes. It is based on Ant Colony Optimization (ACO) meta heuristic, which is adopted to enhance the paths with the best-quality function. The assessment of this function depends on multi-criteria metrics such as the minimum residual battery power, hop count, average energy of the route and average energy of the network. The second one is a Reliable Routing Scheme for Energy- Balancing (RRSEB), which is a self-adaptive scheme to ensure the high routing reliability in WSNs, if the failures occur due to the movement of the sensor nodes or due to sensor node’s energy depletion. The RRSEB operations focus on enhancement of the path recovery process, this is done by introducing proactively route mechanism to create alternative paths together with the data routing obtained by path discovery stage in order to reduce the packet drops. The goal of these operations is to update and offer new routing information in order to construct the multiple paths resulting in an increased reliability of the system. Finally, we propose Self-Decision Route Selection scheme which is an improvement of the Hop-based Spanning Tree (HST) algorithm that is used in some routing protocols such as AODV and DSR. This scheme utilizes the control packets of HST to advertise the residual energies of the sensors to their respective neighbors in order to make a self-decision routing. By this means sensor nodes transmit the data either to next hop neighbors or directly to the sink node. This load balancing scheme distributes the traffic load regularly and slowly over the sensor nodes during routing, such that the overall network life time is optimized, and the sensors die almost at the same time. The performance of the proposed algorithms has been studied through simulations and a significant improvement in terms of energy consumption, energy efficiency, energy balancing and packet delivery ratio has been achieved. SensorAnt shows superior performance compared to Energy Efficient Ant Based Routing (EEABR). It reduces total energy consumption by 71%, while performance improves by 76% in terms of energy-efficiency. Whereas the RRSEB reduces the packet drops by up to 54% and the energy efficiency improves by up to 22%. Finally, the proposed Self-decision Route Selection scheme reduces the transmission energy usage by up to 64%, while the reception energy usage is reduces by up to 67%.